One-punch man. 29, Rejuvenated offence - ONE, 1986- (One-punch man, 2024)
Nothing about Saitama passes the eyeball test when it comes to superheroes, from his lifeless expression to his bald head to his unimpressive physique. However, this average-looking guy has a not-so-average problem--he just can't seem to find an opponent strong enough to take on! S-class hero Blast suddenly appears before Saitama and Flash in search of a mysterious box! But what is it about the box that has the Hero Association's top hero chasing after it? Meanwhile, several heroes are locked in a fierce battle with Monster Association executives when Genos's power core becomes unstable!